In Vitro Antibacterial Activity of Ethanolic Extract of Aloe Vera and Silver Nanoparticles on Standard Strains of Some Pathogenic Bacteria - Abolfazl jafari-Sales; Parisa Meshinchi; Ali Shabkhosh (Golestan University Of Medical Sciences, 2021)
Background and objectives: Today, with the increasing rate of antibiotic resistance, treatment of bacterial infections has become challenging. Therefore, it is essential to find suitable alternative antibacterial compounds. The aim of this study was to investigate in vitro effects of silver nanoparticles and ethanolic extract of Aloe vera alone and combined on standard strains of some pathogenic bacteria. Methods: After collection and verification of A. vera plants, extraction was performed by the Soxhlet extractor method. Antibacterial effects of ethanolic extract of A. vera and silver nanoparticles on standard strains of Staphylococcus aureus, Bacillus cereus, Escherichia coli and Pseudomonas aeruginosa were investigated by agar well diffusion and tube dilution methods, respectively. Results: The ethanolic extract of A. vera and silver nanoparticles had antibacterial effects on the tested bacteria in a dose-dependent manner.  The ethanolic extract of A. vera was more effective against S. aureus and B. cereus compared to gram-negative bacteria. However, silver nanoparticles were more effective against gram-negative bacteria (P. aeruginosa and E. coli). The effect of combination of ethanolic extract of A. vera and silver nanoparticles was much greater than the effect of either alone. This combination showed the greatest and lowest effect on P. aeruginosa and S. aureus, respectively. Conclusion: For the first time, this study showed that the combination of ethanolic extract of A. vera and silver nanoparticles is effective against potentially pathogenic bacteria. Given the high rate of antibiotic resistance and side effects of conventional antibiotics, it is recommended to identify active compounds of this plant and evaluate the antimicrobial effects of this combination of fungi and other pathogenic bacteria both in vitro and in vivo.